Improving the Speaking Ability with the Discussion Method in Social Sciences Subjects - Listiana, Selvia (Jurnal Primagraha, 2020)
This research goal is to know whether students speaking ability could be improved through  On social science of Grade VI students of SD Negeri Angkasa I by using the discussion method. This type of research is classroom action research (CAR). The subjects in this study were students of class VI SDN Angkasa I, amounting to 23 students. The object of his research was students' speaking ability using the discussion method. The research design used is Kemmis and Mc. Taggart. This research was conducted in two cycles. Each action consists of three meetings. In each cycle there are four stages, namely planning, action, observation, and reflection. Data collection techniques in this study through verbal tests and observations. The data analysis technique used in this research is descriptive qualitative. The results showed that the discussion method can improve speaking skills in fifth grade students of SD Negeri Angkasa I. This can be seen in increasing students' speaking abilities. In the pre-cycle average value obtained was 69.34 (with the initial condition of only 6 students whose grades exceeded the KKM) the increase in the average value of the first cycle was 74.13 and an increase in completeness with an average of 80.17 in the cycle II.